On Some Forward-Backward Diffusion Equations (Journal of Partial Differential Equations, 2006)
We describe an application of the partial differential inclusion method to the existence of Lipschitz weak solutions for certain forward-backward diffusion equations including the one-dimensional version of the Perona-Malik equation in image processing.
Keywords: forward-backward diffusion equation; partial differential inclusion; relaxation property; existence of weak solutions; image processing